RETHINKING PRESCRIPTIONS: DESIGNING A CLINICAL PROCESS MAP TO MITIGATE DAPAGLIFLOZIN-INDUCED PRESCRIBING CASCADES - RAVINANDAN AP,; ESWARAN MAHESWARI,; HUNSUR NAGENDRA VISHWAS, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
A 68-year-old man developed fever, breathlessness, and excessive sweating. He is a known case of type 2 diabetes mellitus; recently, dapagliflozin was prescribed. Dapagliflozin reduces blood glucose by inhibiting selective sodium-glucose cotransporter-2. Sometimes, it induces infection due to an excessive amount of glucosuria. The patient’s laboratory report indicates the bacterial infection and prescribes antibiotics. Occasionally, adverse drug reactions (ADRs) are misinterpreted by doctors as new medical conditions or symptoms, adding one more drug to the treatment chart or prescription needlessly, and this process is called the prescribing cascade (PC). This typical case is also the best example for two different types of PCs, such as an intentional, inappropriate, and prophylactic PC, with pantoprazole and ciprofloxacin and tinidazole as an unintentional and appropriate PC. Because of the PC, patients unnecessarily spend money, increasing the treatment cost. A detailed medical and medication history during the consultation and clinical process maps (CPM) will help minimize this advanced stage of ADRs. CPM are one tool generated using different geometric shapes with various colors. Hence, we have designed the CPM, which can play a pivotal role in diminishing the incidence of ADR and PCs by better understanding